2021
DOI: 10.1200/jco.2020.39.28_suppl.77
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of survival disparity between insured and uninsured individuals after the USPSTF's 2012 prostate-specific antigen-based prostate cancer screening recommendation.

Abstract: 77 Background: In 2012, the U.S. Preventive Services Task Force (USPSTF) recommended against prostate-specific antigen (PSA)-based screening for prostate cancer. Studies have found that insured patients with prostate cancer have better outcomes than uninsured patients. We examined the recommendation’s effects on survival disparities based on insurance status as well as socioeconomic quintile, marital status, and housing (urban/rural). Methods: Using the SEER18 database, we examined prostate cancer-specific su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Since studies prior to the recommendation reported that Black patients were almost half as likely to undergo PSA screening than White patients, our findings suggest that lower rates of PSA screening among Black men in the pre-USPSTF era may be an important contributing factor to prostate cancer survival disparities between White and Black men. 3…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since studies prior to the recommendation reported that Black patients were almost half as likely to undergo PSA screening than White patients, our findings suggest that lower rates of PSA screening among Black men in the pre-USPSTF era may be an important contributing factor to prostate cancer survival disparities between White and Black men. 3…”
mentioning
confidence: 99%
“…Since studies prior to the recommendation reported that Black patients were almost half as likely to undergo PSA screening than White patients, our findings suggest that lower rates of PSA screening among Black men in the pre-USPSTF era may be an important contributing factor to prostate cancer survival disparities between White and Black men. 3 In addition to Black patients, uninsured patients comprise a population significantly affected by inequities in prostate cancer outcomes and experience mortality rates almost twice as high as those of insured patients. 4 In a follow-up publication, we found that the USPSTF's 2012 recommendation similarly resulted in the disappearance of survival disparities between insured and uninsured patients.…”
mentioning
confidence: 99%
“…Of the 22 abstracts selected for oral presentations, 13, nearly 60%, were presented by trainees (Fig 1). [1][2][3][4][5][6][7][8][9][10][11][12][13] Five of these trainees were recipients of ASCO's Merit Awards. 14 Presenters came from a variety of backgrounds and included medical students, residents, clinical fellows, master students, predoctoral students, postdoctoral trainees, and junior faculty on career development awards.…”
mentioning
confidence: 99%
“…Although recently there appears to be a controversy regarding the predictive validity of prostate cancer screenings, as well as some contention regarding the association between screening procedures and prostate cancer mortality rates (see Andriole et al, 2009; Getaneh et al, 2020; Pinsky et al, 2019), population studies of prostate cancer screenings have consistently shown a long-term decrease in prostate cancer mortality rates due to screening attendance (Carlsson et al, 2017; Hugosson et al, 2019; Osses et al, 2019; Tabei et al, 2020). Moreover, when the Centers for Disease Control and Prevention (CDC) downgraded their prostate cancer screening recommendation to a “D” grade, evidence suggested that this change led to increases in metastatic prostate cancer and prostate cancer mortality rates due to lower levels of screening attendance and, therefore, decreased detection of dangerous, metastatic prostate cancer (Butler et al, 2020; Joshi & Filson, 2020; I. E. Kim et al, 2020).…”
mentioning
confidence: 99%